In Silico Analysis of Fluoroquinolone Derivatives as Inhibitors of Bacterial DNA Gyrase - Jadán, Evelin (2025)
Antimicrobial resistance represents a mounting global health concern, primarily attributable to the widespread and indiscriminate use of antibiotics. This has led to the emergence of resistant strains and a gradual decline in the clinical efficacy of existing therapeutic agents. In this context, the design of new antimicrobials remains a significant challenge. This study evaluated, using in silico tools, the binding affinity of eight novel fluoroquinolone derivatives against the DNA gyrase of six bacterial species, using moxifloxacin as the reference compound. Target protein sequences were retrieved from the Protein Data Bank and GenBank and subsequently modeled using SwissModel, I-TASSER, and Phyre2. The generated structures were assessed with MolProbity, and those with the best scores were selected for molecular docking. Proteins were prepared using Chimera 1.18 and AutoDockTools 1.5.7. The active site was identified with Discovery Studio 2024. Ligands were built in ZINC, prepared using Open Babel v3.1.1.60, and docked with AutoDock Vina v1.2.3.57. Docking validation was performed with DockRMSD. Considering these results, four new molecules (A1, B1, C1, and D2) were designed to improve their pharmacokinetic properties by modifying the TPSA value of the original structures. However, the new docking assays revealed that these optimized compounds did not exhibit a significant increase in affinity toward the target enzyme. The findings suggest that compound C retains a favorable profile as a potential antimicrobial agent against resistant strains.